Experimental Validation of the Non-Singular Terminal Sliding Mode Controller for a Process Control System - Laware, Ajit Rambhau; Awaze, Sneha Kuldipak; Bandal, Vitthal Shrirang; Talange, Dhananjay Balu (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2023)
This paper presents the design of a non-singular terminal sliding mode control (NTSMC) algorithm to process a tank system which ensures high robustness, non-singularity, and finite-time convergence. The proposed control method and modified sliding manifold remove the problems associated with singularity and value complexity. The stability of the proposed strategy is proven via Lyapunov analysis, which explores the conditions for a sliding surface and error convergency in finite time to an equilibrium point or origin. The control performance of the proposed method is comparable with classical terminal sliding mode control (TSMC) and typical continuous-time sliding mode control (SMC). The simulation and experimental results reveal the efficacy of NTSMC for estimating parameters, set-point changes from one level to another, and external disturbances. The comparison shows better process speed, settling time, rise time, non-overshoot response, and reduced chattering.